'A Very Difficult Troublesome Affair': Some Unlikely Help for the Pretender. Issue 1 (May 2021) - Cain, Robert
Abstract : In April 1746, only weeks after th e decisive defeat of the Jacobite army at Culloden, a British warship, HMS Triton, stopped the Gordon, a suspicious-looking ship off Scotland's northwestern coast, near Skye. The strange craft proved to have been taken over on a voyage to America by its human cargo of Irish indentured servants – men, women and children – some 113 souls, with the intention of joining the Stuart rebel forces in Scotland. After taking the servants as prisoners, Captain Brett of the Triton had to confront the question of how to clear his ship of the unwelcome guests, a dilemma that included such questions as ownership, jurisdiction, claims to compensation, and lines of authority. After weeks of frustration, all was finally resolved by the discharging the bulk of the prisoners to Carrickfergus Castle. Brett was able to resume his naval duties, and most of the servants were soon back on their way to a life in the colonies. This incident, minor as it was in itself, is a possibly unique example of political expression by members of the Irish underclass during the Jacobite insurrection of 1745.